Soil Structure Interaction Effect in Foundations (Journal of Science and Engineering, 2026)
A foundation transfers a portion of a structure's weight to the earth. The traditional method of isolated and eccentric footing has been replaced by mat foundation in recent trends. Nevertheless, the concept of soil structure interaction (SSI), which refers to the qualities of the soil in contact with the foundation, has not been implemented in detail in reality. Research has shown that integrating soil structure interaction (SSI) has a major impact on a structure's performance. Winkler’s approach was employed in our work to mimic the spring-like foundation soil. This study details how several foundation types, including combined footing, strap footing, and eccentric isolated footing, affect the RC-frame structure's dynamic properties, including base shear, roof displacement, and natural time period. For all foundation types, the SSI impact revealed an increase in the structure's roof displacement; however, the effect is more pronounced in the case of an eccentric isolated foundation. Roof displacement was used as a performance criterion to assess the constructions' performance. This research analyses changes in base shear, roof displacement, and natural time period as a result of taking SSI into consideration. It ends with a call for SSI to be taken into account in structural analysis and design.